Larvicidal and Repellent Activities of Crude Extracts and Essential Oils from Eupatorium odorata Against Aedes aegypti, Culex quinquefasciatus and Anopheles dirus B - หาญภาคภูมิ, ดร.ศรีสุดา; กันหาจันทร์, ดร.ภานุกิจ; ภักดีนวน, พายุ; โทผล, ผู้ช่วยศาสตราจารย์ ดร.สุชาดา; กระจ่างสังข์, ผู้ช่วยศาสตราจารย์ ดร.สุขุมาภรณ์; ชมพูศรี, ดร.จักรวาล; ธวัชสิน, ดร.อภิวัฏ (Journal of Food Health and Bioenvironmental Science, 2017)
Saabseua (Eupatorium odorata) is a weed that has many biological activities. Therefore, this research was interested in the extraction method and its application for larvicidal (3rd and 4th instar larvae) and repellent activities against Aedes aegypti, Culex quinquefasciatus and Anopheles dirus B. The leaf, stem and root parts of E. odorata were extracted by using water, ethanol and methanol as solvents. The results showed the yield of crude extract from leaf by methanol was 29.19±2.71 %, which was significantly higher than other solvents. Moreover, the yield of essential oil extracted from leaf (0.25±0.015 %) was significantly higher than from the stem and root. The crude extract from the ethanol root extract exhibited moderate larvicidal activity against Anopheles dirus B and Cx. quinquefasciatus. While, the crude extract from leaf by methanol found high tannins and saponins which demonstrated moderate repellent activity against Cx. quinquefasciatus. The essential oil extracted from leaf showed moderate larvicidal activity against Anopheles dirus B. However, the protection times of essential oil extracted from leaf at the concentration of 0.60 mg/cm2 of skin was 107.67 ± 3.72, 95.00±3.28 and 83.0±3.16 min against Cx. quinquefasciatus, An. dirus B and Ae. aegypti, respectively. The main components of essential oil extracted from leaf was caryophyllene oxide, t-muurolol and humulene epoxide; these components are suitable for development of the natural repellent product.